The Role of Pharmacists in Emergency Health Care Systems: Collaboration with Nurses, EMTS, and Epidemiologists - Almutairy , Nawaf Mabrok N; Alanazi , Abdulelah Saad K; Al-Sharari, Salman Mohammed S; Al-Khudhrah , Salem Mohammed A; Al Alshahi , Ali Saleh M; Alyami , Abdullah Mana S; Shreaf , Meshal Mohammed G; Alyami , Hadi Mansour H; Alyami, Ali Mansour H (Journal of Ecohumanism, 2024)
Pharmacists have an important function in emergency care because of their specialist knowledge of medicine use, patient counseling, and public health. Working with nurses, EMTs, and epidemiologists is crucial in increasing patient safety, minimizing mistakes in medication administration, and increasing the efficient use of resources in emergencies. Pharmacists thus intervene in clinical decisions and disease monitoring to improve practice effectiveness and results, especially in acute care situations, emergency departments, and epidemics. This paper aims to outline the importance of pharmacists’ work in emergency care using different sources of literature review and case studies with an emphasis on coordination to enhance the quality of healthcare delivery systems.